根号下(25-x²)-根号下(15-x²)=2 求根号下(25-x²)+根号下(15-x²)

来源:学生作业帮助网 编辑:作业帮 时间:2024/10/09 09:11:53
根号下(25-x²)-根号下(15-x²)=2 求根号下(25-x²)+根号下(15-x²)
x){`Ovtad[lhna~O.!³M85jhTO_ l:fh iEc(FSݬX[3sE[T{x)X)+jysi;n_u=6yv`s!2:H#PbOv@8#MpCYgÓKlaǓL

根号下(25-x²)-根号下(15-x²)=2 求根号下(25-x²)+根号下(15-x²)
根号下(25-x²)-根号下(15-x²)=2 求根号下(25-x²)+根号下(15-x²)

根号下(25-x²)-根号下(15-x²)=2 求根号下(25-x²)+根号下(15-x²)
√(25-x²)-√(15-x²)=2
[√(25-x²)+√(15-x²)][√(25-x²)-√(15-x²)]=25-x²-﹙15-x²﹚=10
∴√(25-x²)+√(15-x²)=10÷2=5
用的平方差公式

根号下(25-x^2)-根号下(15-x^2)乘(根号下(25-x^20)+根号下(15-x^2))=10 所以答案为5

√(25-x²)-√(15-x²)=2
[√(25-x²)+√(15-x²)][√(25-x²)-√(15-x²)]=25-x²-﹙15-x²﹚=10
∴√(25-x²)+√(15-x²)=10÷2=5